Optical Spectra Properties and Continuous-Wave Laser Performance of Tm,Y:CaF2 Single Crystals - Jingxin Ding; Beibei Zhao; Weiwei Ma; Hao Yu; Xiaobo Qian; Lingchen Kong; Jingya Wang; Guoqiang Xie; Anhua Wu; Fanming Zeng; Liangbi Su (International Journal of Optics)
3 at.% Tm, x at.% Y:CaF2 crystals (x=0, 0.5, 1, 2, and 3) were grown by the vertical Bridgman method and investigated. Codoping Y3+ ions can manipulate the local structure of Tm3+ ions in the CaF2 crystal and then improve the spectroscopic properties. Compared with 3 at.% Tm:CaF2, 3 at.% Tm, 3 at.% Y:CaF2 crystal has several advantages. Firstly, the absorption cross section is improved from 0.35 × 10−20 cm−2 to 0.45 × 10−20 cm−2 at 767 nm, and the fluorescence intensity had elevated 3.4 times. Secondly, the linewidth of the fluorescence spectrum and lifetime also increased from 164 nm to 191 nm and from 6.16 ms to 8.15 ms at room temperature, respectively. Furthermore, quantum efficiency improved from 58.2% to 80.3%. The maximum laser output power of 583 mW and slope efficiency of 25.3% were achieved in 3 at.% Tm, 3 at.% Y:CaF2 crystal under 790 nm diode pumping.